Effects of the specialised combined training of running, hurdles and striding in male 400m young hurdle athletes - Shi, D.; An, D.; Rong, J. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. III, 2008)
Introduction: There are a number of benefits of training young 400m hurdle runners with specialized skills for hurdle events. The purpose of this study was to determine the benefits of early specialized training with the combination of running, jumping and striding. In addition, the paper aims to identify athletes who have the ideal physical attributes to compete at the elite level in hurdles. The issue of the impact of specialized training early in an athlete`s career was also explored. Methods The subjects of this study were young males based in Ukraine and the youth sports schools of Hebei province, China. Literature review, testing via experiment were factors used in the study. Statistical analysis was applied to the data. Results The results of the study showed that certain physical factors were correlated highly with skill level and performance in the 400m hurdles. Data analysis showed several major physical indicators that were positively correlated with the sports abilities required in the 400 m hurdles (r=0.600). Seven items of physical indicators were used (height, the length of thigh, sitting height, the length of calf, foot length, body weight, the height of foot arch). In addition, 6 items of physiological factors were measured (systolic blood pressure, diastolic blood pressure, heart rate, VO2max, blood lactic acid, phosphocreatine CK). Ten items of physical performance indicators were studied (30-metre race, 60- metre race, standing long jump, standing long jump of five levels, vertical jumps , 100m back step, 20m single-leg jump, 100, 200, 400m race). Fourteen items of hurdle specific skills were measured (speed of accelerative running after starting (ms); the distance between the starting point of hurdling and the hurdle (cm); the reaction time of the takeoff leg when starting hurdle, (ms); the angle of the takeoff leg`s stepping on land when starting hurdle (degree); the highest point of the body`s gravity centre when attempting to hurdle (cm); the strut time of the supporting leg when falling hurdles (ms); the angle of upper body`s forward obliquity when falling hurdles, (degree); the angle of upper body`s forward obliquity when striding hurdles (degree); the distance between the landing point and the hurdle (cm); speed of hurdle stride, (ms); the running speed between the hurdles, (ms); time needed for the first 200m (s); time needed for the latter 200m (s); Analysis of the relationship between general skill and hurdling ability was based on 37 parameters. Regression analysis was used for further analysis, after t-tests. All the results achieved statistical significance. The regression equation was found: Y= -25.03 + 2.08X1- 0.40X2+ 0.05X3+ 0.93X4 + 0.01X5+ 1.58X6+ 0.34X. The Y stands for the result of 400m hurdle race, X1 stands for a technical coefficient, X2 stands for the result of 400m race, X3 stands for blood lactic acid, X4stands for VO2max, X5 stands for height, X6 stands for the result of the first 200m hurdle race, X7 stands for the result of the latter 200m hurdle race. Conclusions The results of the study suggest that using a combined type of training early in an athletes` career improves their skill level extensively when compared to other standard training methods.